A high-speed low-power rail-to-rail column driver for AMLCD application. - Chih-Wen Lu
A high-speed rail-to-rail low-power column driver for active matrix liquid crystal display application is proposed. An inversion controller is attached to a typical column driver for rail-to-rail operation. Two high-speed complementary differential buffer amplifiers are proposed to drive a pair of column lines and to realize a rail-to-rail and high-speed drive. The output buffer amplifier achieves a large driving capability by employing a simple comparator to sense the transients of the input to turn on an auxiliary driving transistor, which is statically off in the stable state. This increases the speed without increasing static power consumption. The experimental prototype 6-bit column driver implemented in a 0.35-μm CMOS technology demonstrates that the driver exhibits the maximum settling times of 1.2 μs and 1.4 μs for rising and falling edges with a dot inversion under a 680-pF capacitance load. The static current consumptions are 4.7 and 4.2 μA for pMOS input buffers and nMOS input buffers, respectively. The values of the differential nonlinearity (DNL) and integral nonlinearity (INL) are less than 1/2 LSB.
Keywords: 0.35 micron; 1.2 mus; 1.4 mus; 4.2 muA; 4.7 muA; 6 bit; 680 pF; CMOS; LCD driver; Active matrix liquid crystal display; Auxiliary driving transistor; Capacitance load; Differential buffer amplifiers; Differential nonlinearity; Driving capability; Integral nonlinearity; Inversion controller; Low-power column driver; nMOS input buffers; pMOS input buffers; Rail-to-rail column driver; Static power consumption